Blood urea nitrogen as a predictor of mortality in myocardial infarction - Liong Boy Kurniawan; Uleng Bahrun; Fitriani Mangarengi; Darmawati E R; Mansyur Arif (Universa Medicina, 2013)
INTRODUCTIONBlood urea nitrogen and creatinine levels are routine laboratory tests for evaluating renal function. Renal dysfunction has been related to worse prognosis of cardiovascular diseases. The purpose of this study was to determine the relationship between admission blood urea nitrogen and creatinine levels with in-hospital mortality in acute myocardial infarction patients. METHODSA cross-sectional study was performed using secondary data of 80 acute myocardial infarction patients hospitalized in Intensive Cardiac Care Unit of dr. Wahidin Sudirohusodo Hospital, Makassar, from June 2010 to July 2011. Admission blood urea nitrogen and creatinine levels were analyzed with Mann Whitney and Chi-Square tests.RESULTSMortality risk in the patients with blood urea nitrogen levels >50 mg/dL was 3.58 higher compared with those with blood urea nitrogen levels <50 mg/dL [OR=3.58; 95% confidence interval (CI) =1.27-10.11, p=0.013]. Mean admission creatinine levels in surviving and non- surviving patients were 0.99 ± 0.30 mg/dL and 1.70 ± 1.99 mg/dL, respectively (p=0.043). Mortality risk in patients with creatinine levels >1.1 mg/dL was 3.0-fold higher compared to patients with creatinine levels <1.1 mg/dL [OR=3.00; 95% confidence interval (CI) =1.13-7.92, p=0.024]. Multiple logistic regression showed blood urea nitrogen to be a better predictor of mortality than creatinine (OR= 3.583, p=0.016 vs OR 1.844, p=0.317).CONCLUSIONSPatients with high levels of blood urea nitrogen and creatinine had higher mortality risks than patients with normal levels. Blood urea nitrogen was a better predictor of mortality than creatinine.